HUBUNGAN PENGETAHUAN DAN MASA KERJA DENGAN GANGGUAN MUSKULOSKELETAL PADA PERAWAT DI RUMAH SAKIT - Balaputra, Ishana (MEDICAL JURNAL OF AL-QODIRI, 2020)
A health problem that is often associated with a non-ergonomic workplace is musculoskeletal disorders. This study is aimed to evaluate the relationship between knowledge of ergonomics and job tenurewith musculoskeletal disorders (MSDs) among nurses in hospital. To perform this cross sectional study, 29 nursing personnel who had full inclusion to participate, were taken with total sampling. For collecting data, a verified questionnaire was used to assess knowledge of ergonomics and job tenure, OWAS was used to assess work posture, and NBM was used to assess musculoskeletal disorders. Data analysis used chi square for bivariate and logistic regression for multivariate test. Bivariate analysis showed there was no significant relationship between gender, age, and education level with musculoskeletal disorders (p>0,05). The relationship between knowledge of ergonomics, work posture, and job tenure with musculoskeletal disorders ware significant (p<0,05). Multivariate analysis showed the significant relationship between knowledge of ergonomics, work posture, and job tenure with musculoskeletal disorders together (p=0,000) with a contribution of 41.07% (R2 0,4107).Education and training on proper ergonomics and work posture should be introduced in the workplace to reduce the risk of musculoskeletal disorders (MSDs) among the nurses working in different settings. Keywords: knowledge of ergonomics,musculoskeletal disorders, job tenure, work posture, nurses